スカイラジオメーター ヲ ツカッタ ニーオルスン ニ オケル エアロゾル ノ コウガクテキ トクセイ ノ チョウキ カンソク - 青木, 一真; アオキ, カズマ; 矢吹, 正教; ヤブキ, マサノリ; 塩原, 匡貴; シオバラ, マサタカ; Aoki, Kazuma; Yabuki, Masanori; Shiobara, Masataka (2010)
P(論文) 北極に位置するニーオルスンでは,2000年3月より現在までスカイラジオメーター観測を行っている.本研究は,ニーオルスンのエアロゾルの光学的厚さとオングストローム指数の時間変化を示す.長期観測の結果によると,0.5 μmのエアロゾルの光学的厚さは,春に最大で夏の終わりに最小となり,オングストローム指数は春から夏にかけて増加するような季節変化が示された. Sky radiometer measurement has been continued at Ny-Alesund, Svalbard (78.93N, 11.86E, Alt. 30 m) in the Arctic region, since March 2000. In this study, we present the temporal variation and the relationship of Angstrom parameters (i.e., aerosol optical thickness and Angstrom exponent) at Ny-Alesund. The results of long-term measurements show clear seasonal trends of the aerosol optical thickness at 0.5 μm with maximum in spring and minimum at the end of summer, and of the Angstrom exponent with temporal increase in spring to summer. departmental bulletin paper